Curcumin analogues attenuate Aβ25-35-induced oxidative stress in PC12 cells via Keap1/Nrf2/HO-1 signaling pathways. (25th May 2019) - Xu, Jialin; Zhou, Leilei; Weng, Qi; Xiao, Linxia; Li, Qingyong
Abstract: Beta-amyloid (Aβ) has pivotal functions in the pathogenesis of Alzheimer's Disease (AD). In the present study, we adopted an vitro model that involved Aβ25-35 -induced oxidative damage in PC12 cells. Aβ25-35 (10 μΜ) treatment for 24 h induced significant cell death and oxidative stress in PC12 cells, as evidenced by cell viability reduction, LDH release, ROS accumulation and increased production MDA. (1E, 4E)-1, 5-bis(4-hydroxy-3-methoxyphenyl) penta-1, 4-dien-3-one (CB) and (1E, 4E)-1-(3, 4-dimethoxyphenyl)-5-(4-hydroxy-3, 5-dime-thoxyphenyl) Penta-1, 4-dien-3-one (FE), two Curcumin (Cur) analogues displayed neuroprotective effects against Aβ25-35 -induced oxidative damage and cellular apoptosis in PC12 cells. Here, we investigated three different treatment ways of CB and FE. It was interesting that post-treatment of CB and FE (restoring way) showed similar effect to the preventive way, while attenuating way did not show any protective effect. We found that low dose CB and FE increased transcriptional factor NF-E2-related factor 2 (Nrf2)/hemo oxygenase 1 (HO-1) protein expression and decreased Kelch-like ECH-associated protein 1 (Keap1) in PC 12 cells. In addition, CB and FE promoted the translation of Nrf2 into nuclear and enhanced the activity of superoxide dismutase (SOD)/catalase, which confirmed cytoprotection against Aβ25-35 -induced oxidative damage. Moreover, CB and FE could increase Bcl-2 expression level, decrease the level of Bax and Cyt-c in Aβ25-35 -treated PC12 cells. Ultimately, the neuroprotective effect of CB and FE provides a pharmacological basis for its clinical use in prevention and treatment of AD. Highlights: Mono-carbonyl analogues of curcumin, CB and FE, exhibited equivalent cytotoxicity in very low dosage compared to Cur. Low dose CB and FE played neuroprotection against Aβ25-35 -induced oxidative stress. CB and FE functioned through both antioxidant and anti-apoptosis pathways.